(untitled) (Palíndromo, 2021)
This text addresses the creative process of the short film Origami (2019), transcreated of the micro tale Devir. The case study is subsidized by Genetic Criticism (SALLES, 2008), in theory of Transcriation (CAMPOS, 2011) and in the thought of Deleuze about the Dobra. Amalgamating the concept of origami from design to cinema, folding cinema is obtained.